Balancing dreams and reality: bridging the gap between parental aspirations and children's interests / Norizam Ahmad @ Muhammad - Ahmad @ Muhammad, Norizam (Fakulti Perakaunan, 2023)
Every child is born with a unique set of talents and passions. These talents and passions may be shaped by their genes, environment, or their experiences. As children grow up, they are exposed to their parents' dreams and expectations. These dreams and expectations can be explicit, such as when a parent tells their child that they want them to be a doctor or a lawyer. Or, they can be implicit, such as when a parent values academic achievement and success over other things.